Practice of preventive measures and vaccine hesitance for COVID 19 among households in The Gambia, 2021: Study protocol. - Bakary Sanneh; Sainey Sanneh; Sharmila Lareef-Jah; Buba Darboe; Lamin L Dibba; Lamin F Manjang; Yorro Bah; Jalimory Suso; Phebian Ina Grant Sagnia; Modou Njai; Sana M Sambou (PLoS ONE, 2022)
The first imported confirmed case of COVID 19 was reported in The Gambia on 16th of March 2020 which led to the implementation of relevant public health interventions to prevent further importation and spread of the virus. However, by 8th November 2021, the country had registered cumulatively 9.980 COVID-19 confirmed infection and 341 deaths. The country has developed and implemented Risk Communication and Community Engagement (RCCE) Action Plan since the declaration by WHO that COVID-19 outbreak was a global public health threat and its subsequent proclamation that outbreak was a pandemic. Despite these efforts to sensitize the communities, some Gambians are in denial and/or misinformed of the existence of infection in the country. It is also evident that social distancing and other restrictions have not been adequately implemented by the citizenry. Less 14% of The Gambian population have been vaccinated, and there is evidence of gross vaccine hesitancy and disbelief. There is urgent need to investigate the knowledge, attitude and practices among Gambians about preventive practices especially regarding accepting vaccination to control COVID 19. The proposed study will enrol 1200 households from seven Local Government Areas (LGAs). The findings of this study will inform the messaging and health promotion activities that will be used to better inform the population to ensure compliance and practice of preventive approaches (e.g., use of mask, vaccination)necessary to reduce the negative impact of COVID 19 outbreak in The Gambia. This will thus quicken the recovery process and the return to new normal life.